Incidence, Mortality, and Burden of Severe Acute Respiratory Infection in Iran in 2015 - Bakhtiar PIROOZI; Cyrus ALINIA; Ghobad MORADI; Hossein SAFARI; Payman HEMMATI; Mahmoud SEROUSH; Hossein ERFANI; Hossein AKBARI; Farshid REZAEI; Mohammad Naser DADRAS; Siroos HEMMATPOUR; Rasool NASIRI KALMARZI (Tehran University of Medical Sciences, 2019)
Background: Severe Acute Respiratory Infection (SARI) is responsible for mortality and hospital admissions in millions of people across the world. The present study, for the first time, aimed at estimating the incidence, mortality, and burden of SARI in Iran in 2015. Methods: Disability Adjusted Life Years (DALYs) was used as an index to estimate the burden of SARI. The SARI-related DALYs was calculated using a method developed by the WHO for assessing the Global Burden of Diseases. DALYs are calculated as the sum of the Years Lost due to Disability (YLDs) and the Years of Life Lost (YLLs) due to premature mortality. The data on the incidence and mortality were obtained from the SARI surveillance system of Iran's Ministry of Health and Medical Education. The average duration until remission or death and the disease disability weight were set at four weeks and 0.373, respectively. Results: In 2015, the incidence of SARI was 21309 and 20885 among males and females, respectively. Moreover, 773 males and 737 females died from this disease (Case fatality rate was about 0.035). Total SARI-related DALYs in males and females was 17264 and 16720, respectively. Furthermore, YLLs was responsible for more than 96% of SARI-related DALYs in 2015. Conclusion: There was no significant difference between males and females in terms of the incidence, mortality, and burden of SARI in 2015. Epidemiological data are required to adopt appropriate policies and responses to prevent and control SARI. The incidence, mortality, fatality, and burden of SARI are significant in Iran. It is necessary to develop appropriate strategies, such as vaccination against major pathogens of the disease at least in high-risk groups, strengthening the disease surveillance system, and attracting the attention of policy makers and health authorities of the country.